Upregulated lncRNA ADAMTS9‐AS2 suppresses progression of lung cancer through inhibition of miR‐223‐3p and promotion of TGFBR3. Issue 6 (29th April 2018) - Liu, Chao; Yang, Zuozhang; Deng, Zhiyong; Zhou, Youjun; Gong, Quan; Zhao, Ruilian; Chen, Ting
Abstract: In this study, we aimed at investigating effects of lncRNA ADAMTS9‐AS2 on lung cancer progression through regulating miR‐223‐3p and TGFBR3 expressions. Expressions of ADAMTS9‐AS2 in lung cancer tissues and cell lines were determined by reverse transcriptase polymerase chain reaction (qRT‐PCR). TargetScan and miRcode were used to predict the targeting relationships, respectively. The luciferase reporter system was used to verify that the relationship among ADAMTS9‐AS2, TGFBR3 and miR‐223‐3p. Western blot assay tested the protein level changes in TGFBR3 . Cell proliferation was determined by CCK‐8 assay. Cell cycle and cell apoptosis were detected by flow cytometry assay, and migration and invasion were determined by transwell assay. Tumor xenograft model was developed to study the influence of ADAMTS9‐AS2 on tumor growth in vivo . qRT‐PCR results demonstrated that lncADAMTS9‐AS2 was lowly expressed in lung cancer tissues. High expression of ADAMTS9‐AS2 in lung cancer cells significantly reduced proliferation ability and inhibited migration, as well as elevating their apoptosis rate. In vivo assay found that ADAMTS9‐AS2 suppressed the lung tumor growth. Bioinformatics predicted that miR‐223‐3p bound directly to the ADAMTS9‐AS2 and TGFBR3, which was later confirmed by luciferase reporter system. ADAMTS9‐AS2 transfection increased TGFBR3 mRNA and protein expressions in lung cancer cells, but miR‐223‐3p transfection significantly decreased them. Besides, our results showed that miR‐223‐3p induced cellular apoptosis while TGFBR3 group showed the complete opposite effect. It was proved that ADAMTS9‐AS2 and TGFBR3 were the direct genes of miR‐223‐3p. MiR‐223‐3p promotes proliferation, migration and invasion of lung cancer cells by targeting TGFBR3 . Therefore, ADAMTS9‐AS2, miR‐223‐3p and TGFBR3 may provide potential targets for the treatment of lung cancer patients. © 2018 IUBMB Life, 70(6):536–546, 2018